PERAN PEMERINTAH DAERAH DALAM MEWUJUDKAN PEMBANGUNAN INFRASTRUKTUR PENDIDIKAN (Suatu Studi di Sekolah Menengah Atas (SMA/MA) Kota Tidore Kepulauan) - Haji, Edi; Kiyai, Burhanuddin; Pombengi, Jericho (Sam Ratulangi University, 2015)
Abstract : This study aims to determine how the development of educational infrastructure (SMA / MA) and the role of local government in terms of infrastructure (infrastructure) education in secondary school (high school / MA) in Tidore Islands.The method used in this research is descriptive qualitative method. The study was conducted at the Department of Education, 4 high schools (SMA / MA), drawn from 26 schools in Tidore Islands and community education observers, thus the total number of informants is 11 people, while collecting data using interview techniques, techniques analysis used is qualitative analysis interactive model of Miler and Huberman.Based on the results of the study it can be concluded that: openness or transparency of school in terms of development, so that the circumstances in which every person associated with the interests of education in schools can know the process and the results of school policy, it is, do not lie, do not cheat, honest, and open to public about what is done by the school. This openness is indicated in decision-making, planning and implementation of activities, the use of the budget and so on, which always involves the relevant parties as a means of control in order that development is not hampered because of the openness or transparency. Based on the results of research it is recommended suggestions: increasing dedication / contribution of stakeholders for education in schools, either in the form of services (thought / intellect, skills), moral, financial, and material / goods. empower the existing capabilities in the education stakeholders to realize the goal of education. enhance the role of stakeholders in the provision of education in schools. ensure that all decisions and measures taken truly reflect the aspirations of stakeholders and make the aspirations of stakeholders as commander for the implementation of development education in schools. The school must mobilize community participation in the form of anything that is relevant in the implementation of school programs, both physical and non-physical form in order to increase the participation of people divided into two categories, namely participation in the form of financial contribution and participation in the form of thought and effort.Key words : The role of Government, Education Infrastructure Development